Silicon nanoparticles obtained via a low temperature chemical "metathesis" synthesis route and their lithium-ion battery properties. Issue 12 (11th February 2015) - Wang, Liangbiao; Lin, Ning; Zhou, Jianbing; Zhu, Yongchun; Qian, Yitai
<x xml:space="preserve">Abstract</x> Silicon (Si) nanoparticles have been prepared by a "metathesis" reaction of magnesium silicide (Mg2Si) and zinc chloride (ZnCl2) in an autoclave at 300 °C.